RANCANG BANGUN PENGENDALIAN SUHU DAN INTENSITAS CAHAYA PADA KANDANG ANAK AYAM RAS PETELUR MENGGUNAKAN MIKROKONTROLER ESP32 - Dio Izqhaq Risky Sasongko; n/a Nurussa’adah; Ali Mustofa (Jurnal Mahasiswa TEUB, 2023)
Temperature is a very important factor during brooding, because it can affect the productivity of the chickens later. Not only the temperature that needs attention, but the lighting in the cage greatly affects the development of chicks to increase feed and water intake. The intensity of light also depends on the behavior / habits of the chickens. Required control of temperature and light in laying hens' cages is expected to make it easier for breeders or laying hens business actors in the process of maintaining temperature and light intensity in the coop so that it remains stable and can change the working system of laying hens breeders which are still manual to become automatic and more efficient . Each sensor is tested to test the error value with standard measuring instruments on each sensor. The DHT11 sensor gets an error value of 1.23% and the BH1750 sensor gets an error value of 0.96%. ESP32 as a microcontroller that processes data from the two sensors is then displayed on the Arduino IDE serial monitor which will later control temperature conditions and light intensity using a solid state relay to control the on/off of the 2 lights used, namely heating lamps and lighting lamps and will work as needed according to the age of the chicks. Keywords: Laying chicks, temperature, light intensity, DHT11 sensor, BH1750 sensor, ESP32, solid state relay, heating lamp, lighting lamp.